PERCEPTUAL MAPPING DAN KORESPONDENSI PRODUK PEMBIAYAAN BMT DANA MENTARI PURWOKERTO - Safrani, Yoiz Shofwa (Fakultas Dakwah IAIN Purwokerto, 2014)
The success of Islamic banking in Indonesia cannot be separatedfrom roles of Islamic microfinance institutions or Lembaga Keuangan Syariah(LKMS). Although the concept of establishment of BMT is intended to be usefulto the society but on the other side in the application there are many BMTâ€™s outof line, in general management has orientation towards profit oriented. Â That phenomena causing BMT should be compete with all different forms and structures of conventional financial institutions and Islamic financial institutions. The competition are to get the good customer for funding and financing. To win the competition, BMT prosecuted to provide optimal service to their customers. This field research aims to see the mapping of Funds Product of BMT Dana Mentari as the biggest BMT in Purwokerto among its competitors with multidimensional scalling analysis and correspondences. The result of spatial mapping was the BMT Khonsa is located on quadrant with a value of dimension 2 is positive and valued of dimension 1 is negative, BMT Dana Mentari is located on quadrant with a value of dimension 2 is positive and the value of dimension 2 is positive, BMT El Mentari is on a quadrant with a value of dimension 1 is negative and neither the values of dimensions 2, BMT Buana Emas is located on quadrant with the value of dimension 2 is negative and the values of dimension 2 is positive. The conclusion are each BMT are on the different quadrants so it doesnâ€™t become a major competitor to the other and there are not similarities between BMT Dana Mentari with other BMT.